DICCIONARIO ENCICLOPEDICO SALVAT - Salvat, Juan (dirección) (SALVAT, 1950)
CONTENIDO: V. 1 A-ANS. -- V. 2 ANT-BEK. -- V. 3 BEL-CAR. -- V. 4 CAS-CHU. -- V. 5 D-EPW. -- V. 6 EQU-FZ. -- V. 7 G-IMU. -- V. 8 IN-MAO. -- V. 9 MAP-OZ. -- V. 10 P-RIZ. -- V. 11RO-TIM. -- V. 12 TIN-Z